Toxicological effects and accumulation of cadmium and lead in the terrestrial isopod, Porcellio laevis Latr. (Crustacea, Isopoda) - Odendaal, James Philander (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.